Modelagem numérica e otimização de shunts piezelétricos aplicados ao controle passivo de vibrações - Santana, Danuza Cristina (2007)
Due to the development of new technologies, industrial structures are now made of lighter materials and work at higher operation speeds producing an increasing vibration and noise level generation. As a result, different techniques of active and passive control have been developed and are continuously being improved. Among the passive control techniques, the use of piezoelectric materials combined with passive shunted circuits has been successfully used. In this kind of control, a piezoelectric patch, generally PZT, is bonded to the surface of the base structure and connected to an electrical circuit in such a way that the vibratory energy is transferred to the piezoelectric patch, The piezoelectric effect makes possible to transform strain energy into electric energy that is dissipated through the Joule effect. The most used shunt topologies are the resistive, resonant, capacitive, switched and the negative capacitance. This technique is appropriate for the control of light structures and does not exhibit instability problems. In this context, this work considers the finite element modeling of structural systems combined with piezoelectric ceramics for different topologies of shunt circuits. In this approach, various aspects of unimodal and multimodal control have been investigated, as the number of piezoelectric patches and their positioning along the structure. As the functioning principle is based on the transfer of strain from the base structure to the PZT, it follows that the control systems efficiency depends on the bonding characteristics (thickness, stiffness, and eventual delamination). Consequently, the influence of the attachment characteristics on the control system efficiency is also investigated in this work. The analyses have been performed by using a finite element code built in MATLAB® and also using the software ANSYS®. Beam and plate like structures are studied, for which the vibration attenuation level is investigated by performing harmonic analyses.